تطبيق متطلبات إدارة المعرفة وأثرها على الأداء الوظيفي دراسة تطبيقية على المصرف التجاري الوطني الليبي - عبد الجواد , عبد السلام محمد (Scientific Journal of University of Benghazi, 2022)
This paper aims to recognition of the requirements of knowledge management and their impact on job performance in the Libyan National Commercial Bank. The proportional stratified sample technique was used to collect data for this research study. The number of (235) questionnaires were distributed and the number of valid questionnaires that entered for processing and analysis were (195). To check the association between requirements of knowledge management and job performance, Pearson correlation statistical technique and regression analysis were applied on the data. The results of the study indicate that the bank operates within a regulatory environment that includes many elements and variables that help in the application of knowledge management in the National Commercial Bank was high, and the requirements of knowledge management, organizational structure, organizational culture, organizational leadership, and information technology have a positive impact on job performance. Also, the study showed that the performance of employees in the bank under study was not high, and the results of testing the main hypothesis and its sub-hypotheses, showed that there is a statistically significant effect of the requirements of knowledge management (organizational structure, organizational culture, organizational leadership, information technology) on the job performance at the National Commercial Bank at a significant level (0.05 ≥ α). The study recommended investing in the positive relationship between the variables of the study, because there is a correlation between them, and the positive impact of knowledge management requirements on the job performance of the bank, which will be positively reflected in improving the performance of the bank in general, as this relationship should be maintained and improvements made in line with the changes. environmental.